(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This paper is a brief summary of the historical trajectory of the Hacienda of Cuisillos, Jalisco. The interest in such property lies, firstly, to contribute to historiographical knowledge about the central area of the state of Jalisco, and secondly, to make relevant the changes and continuities experienced in a farm such as Cuisillos along its nearly 400 years, similar to other large properties in western Mexico. The work begins with an overview of how the property was consolidated, emphasizing its important role, especially for the supply of Guadalajara, capital of the vast territory then known as Nueva Galicia. Then continues with an analysis of the property after different owners own the place throughout the colonial era and during the independence period. Finally, we conducted a breakdown of how Cuisillos lost their land to peasants living in villages and peons of the haciendas. Haciendas that had monopolised the land in the Valley of Tala.